Reflective Teacher Journal to Develop Teacher’s Professionalism - Anjar Nur Cholifah; Abdul Asib; Suparno Suparno (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
To be good a teacher, a teacher must incessantly improve her/his teaching practice and skill/knowledge to produce and keep the academic quality. Mechanically, a teacher requires to concern a particular method/ technique or strategy and use a certain tool/type to fulfill the benchamark of excellence in teaching. Hence, reflection is substantial as one of the indispensable approaches that can be practiced to direct teacher’s performance becomes more experienced. In teaching, the term reflection refers to the opportunity of teachers to think back critically after the teaching-learning process. Previous studies that have been conducted to observe the efficiency of teacher journal in the education field. Conversely, only a few kinds research explored teacher’s perceptions toward the utilization of the teacher’s journal. Likewise, this research was located in Indonesia and engage an in-service EFL teacher of Junior High School to accomplish the gap. It intended at determining the parts reflected from the teacher journal. Moreover, to investigate the research problems, the researcher used an in-depth interview to explore the teacher’s experience in utilizing teacher diary. Consequently, this study employed a qualitative method since it was considered as the appropriate design to accomplish the research. The researcher concluded that the teacher has a positive perceptions related to the teacher’s diary/teacher’s journal. It gives precious involvement for English teachers to be more experienced and professional to help students in mastering English skills and help the teacher to do reflection in order to make a better teaching practice for the next English teaching.